Parentético e outras unidades informacionais curtas: uma distinção através da análise das diferentes realizações prosódicas do lexema ASSIM - Saulo Mendes Santos (2020)
This thesis aimed at analyzing the Informational Unit of Short Parenthetical (short PAR) and other short informational units (defined as an isolated phonological word in a dedicated intonational unit) as defined within the theoretical framework of the Language into Act Theory (CRESTI, 2000; MONEGLIA & RASO 2014) in order to describe the prosodic patterns associated with different functions. Short PAR is functionally characterized by inserting instructions on how to interpret the utterance or part of it (CRESTI, 2000; TUCCI, 2009; MONEGLIA & RASO, 2014). All short units are generally treated as short PAR. Although they may belong to various classes, lexical fillers of short PAR are generally frequently used expressions. As a rule, the literature (DEHÉ, 2014; KALTENBÖCK, HEINE & KUTEVA, 2010; SCHNEIDER, 2007) defines PAR based on syntactic and lexical criteria, and seeks accordingly to differentiate them into subfunctions. However, when prosody is taken into account, the functions confused with PAR can be set off without resorting to these criteria. In this work, we decided to test this hypothesis by analyzing only the lexeme ASSIM (like this, so) since it is the most frequent in the corpus used, the C-ORAL-BRAZIL I (RASO & MELLO, 2012). We found out that it may fulfill functions of PAR, different discourse markers (mainly, but not only, conative), locutive introducers, and appendices of comment. Each function corresponds to a defined prosodic form, also accompanied by distributional constraints and specific semantic correlates. Prosodic profiles of all occurrences were analyzed with the software Praat (WEENINK & BOERSMA, 2019). Occurrences were organized into prosodically and functionally consistent groups, and, finally, quantified. As a result, the following groups of consistent prosodic and functional behavior were obtained: a) a flat f0 profile with a semantic-textual function of PAR, the largest group; b) a profile with falling f0 movement and high articulation rate with the function of introducing meta-illocutions and lists, the locative introducer; c) a falling f0 profile aligned with the stressed syllable with an interactional function (drawing the addressee's attention to the actional solution of the utterance), the conative, quite frequent; d) a rising f0 profile with interactional function (maintenance of the communicative channel), a discursive marker not yet described; and e) a falling f0 profile with a seemingly time-taking function. In addition, we found that the lexeme tends to constitute a final support in intonational units, especially those with illocutionary force. This thesis presents the audios, prosodic profiles, and functions of the most paradigmatic examples of each group.